Exome sequencing establishes a gelsolin mutation as the cause of inherited bulbar‐onset neuropathy. Issue 5 (23rd March 2017) - Caress, James B.; Johnson, Janel O.; Abramzon, Yevgeniya A.; Hawkins, Gregory A.; Gibbs, J. Raphael; Sullivan, Elizabeth A.; Chahal, Chamanpreet S.; Traynor, Bryan J.
ABSTRACT: Introduction: Progressive bulbar motor neuropathy is primarily caused by bulbar‐onset ALS. Hereditary amyloidosis type IV also presents with a bulbar neuropathy that mimics motor neuron disease. The disease is prevalent in Finland only and is not commonly included in the differential diagnosis of ALS. Methods: We studied 18 members of a family in which some had bulbar motor neuropathy, and we performed exome sequencing. Results: Five affected family members were found to have a D187Y substitution in the GSN gene known to cause hereditary amyloidosis type IV. Conclusions: This American family presented with progressive bulbar neuropathy due to a gelsolin mutation not found in Finland. Hereditary amyloidosis type IV presents with bulbar motor neuropathy and not with peripheral neuropathy as occurs with common forms of amyloidosis. This report demonstrates the power of exome sequencing to determine the cause of rare hereditary diseases with incomplete or atypical phenotypes. Muscle Nerve 56 : 1001–1005, 2017